(untitled) (Bangladesh Journal of Medical Science, 2012)
Lateral neck swelling is a common presentation in ORL practice. The complexity of the neck structures warrants a thorough examination and investigation to narrow down the differential diagnosis. Neoplasm need to be ruled out especially if the neck swelling present in an adult. We report a case of a lateral neck mass being treated as lymphadenopathy before the patient defaulted follow up. The patient represented after 3 years and investigations performed. FNAC revealed sialadenosis but radiologically and intra-operatively consistently showed the mass located outside parotid gland. The final diagnosis of Whartin’s confirmed after the HPE evaluation. The diagnosis dilemma is discussed. Keywords: Lateral neck selling; warthin’s tumour; extra parotid DOI: http://dx.doi.org/10.3329/bjms.v10i4.9506 BJMS 2011; 10(4): 296-298